2018
DOI: 10.3892/etm.2018.6076
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasminogen activator inhibitor‑1 in the diagnosis and prognosis of patients with Parkinson's disease

Abstract: Parkinson's disease is a neurodegenerative disease that frequently results in memory disorders, cognitive decline and dementia. Previous studies have reported that plasminogen activator inhibitor-1 (PAI-1) serves an important role in cardiovascular disease risk, adiposity, insulin resistance and inflammation. However, the role of PAI-1 in diagnosis and prognosis of patients with Parkinson's disease following deep brain stimulation (DBS) has not reported, to the best of our knowledge. Therefore, the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…However, when chronically activated, microglia also contribute to neurodegenerative diseases by maintaining neuroinflammation. Several reports have indicated a role of PAI-1 in central nervous system pathology, including multiple sclerosis [ 130 , 131 ], Alzheimer’s disease [ 132 , 133 ], and Parkinson’s disease [ 134 , 135 ]. In demyelinated axons in inflammatory multiple sclerosis lesions, increased PAI-1 levels impair the capacity of the tPA/plasmin system to clear fibrin(ogen) deposits and therefore contribute to axonal damage in multiple sclerosis [ 131 , 136 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…However, when chronically activated, microglia also contribute to neurodegenerative diseases by maintaining neuroinflammation. Several reports have indicated a role of PAI-1 in central nervous system pathology, including multiple sclerosis [ 130 , 131 ], Alzheimer’s disease [ 132 , 133 ], and Parkinson’s disease [ 134 , 135 ]. In demyelinated axons in inflammatory multiple sclerosis lesions, increased PAI-1 levels impair the capacity of the tPA/plasmin system to clear fibrin(ogen) deposits and therefore contribute to axonal damage in multiple sclerosis [ 131 , 136 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…However, we have found that 3 of the ve PD-VPs that interact with it appear upregulated/signicantly-increased in blood (APP [84] and SERPINE1 [85]) or CSF (TGFB1 [86]) of PD patients. The other two PD-VPs are neuroprotective for PD (HGF [87] and TIMP1 [88]).…”
Section: Resultsmentioning
confidence: 76%
“…There is not much information about the possible role that this host protein could have in PD. However, we have found that 3 of the five PD-VPs that interact with it appear upregulated/significantly-increased in blood (APP [ 119 ] and SERPINE1 [ 120 ]) or CSF (TGFB1 [ 121 ]) of PD patients. The other two PD-VPs are neuroprotective for PD (HGF [ 122 ] and TIMP1 [ 123 ]).…”
Section: Discussionmentioning
confidence: 99%